Tetrahymena: An Alternative Model Host for Evaluating Virulence of Aeromonas Strains - Pang, Mao-Da; Lin, Xiao-Qin; Hu, Meng; Li, Jing; Lu, Cheng-Ping; Liu, Yong-Jie (PLOS ONE, 2012)
An easier assessment model would be helpful for high-throughput screening of Aeromonas virulence. The previous study indicated the potential of Tetrahymena as a permissive model to examine virulence of Aeromonas hydrophila. Here our aim was to assess virulence of Aeromonas spp. using two model hosts, a zebrafish assay and Tetrahymena-Aeromonas co-culture, and to examine whether data from the Tetrahymena thermophila model reflects infections in the well-established animal model. First, virulence of 39 Aeromonas strains was assessed by determining the 50% lethal dose (LD50) in zebrafish. LD50 values ranging from 1.3×102 to 3.0×107 indicated that these strains represent a high to moderate degree of virulence and could be useful to assess virulence in the Tetrahymena model. In Tetrahymena-Aeromonas co-culture, we evaluated the virulence of Aeromonas by detecting relative survival of Aeromonas and Tetrahymena. An Aeromonas isolate was considered virulent when its relative survival was greater than 60%, while the Aeromonas isolate was considered avirulent if its relative survival was below 40%. When relative survival of T. thermophila was lower than 40% after co-culture with an Aeromonas isolate, the bacterial strain was regarded as virulent. In contrast, the strain was classified as avirulent if relative survival of T. thermophila was greater than 50%. Encouragingly, data from the 39 Aeromonas strains showed good correlation in zebrafish and Tetrahymena-Aeromonas co-culture models. The results provide sufficient data to demonstrate that Tetrahymena can be a comparable alternative to zebrafish for determining the virulence of Aeromonas isolates.